Comparison of three generalised moment methods for raindrop size distribution modelling - Potuznikova, Katerina; Fišer, Ondřej; Rejfek, Luboš; Potuznik, Cenek; Kovalchuk, Maria; Zikešová, Aneta (IEEE (Institute of Electrical and Electronics Engineers), 2024)
The moment method is a widely used method for calculating statistical parameters that are used to fit the theoretical droplet distribution function (DSD) to the observed droplet size distribution. In this paper we propose both analytical solutions for the parameters of the Gamma and Exponential distribution functions and numerical optimization of the parameters for the Modified Gamma function. When the theoretical distribution functions are applied to real data recorded by the videodistrometer, it is found that the numerical solution of the Modified Gamma function fits well for the smallest droplets and for the middle part of the droplet spectrum, while the region of the largest diameter droplets is better described by the Gamma distribution function. All results contribute to meteorological radar theory and make the radio link design more effective.
Porovnání tří zobecněných momentových metod pro modelování distribuce velikosti dešťových kapek
Keywords: drop size distribution (DSD); radar meteorology; radiowave propagation; rain attenuation; distribuce velikosti kapky (DSD); radarová meteorologie; šíření rádiových vln; útlum deště